Distribution, utilisation and future prospects of some underutilised cucurbits of Jammu and Himachal Pradesh (India). Funded Project - MEHNAZ BANO; GEETA SHARMA (International Journal of Pharma and Bio Sciences, 2017)
Cucurbitaceous species are cultivated on large scale from tropical to sub-tropical regions of the world. In India, along with major cucurbits such as Luffa cylindrica, Citrullus lanatus, Cucurbita pepo, Cucumis melo, C. sativus, Lagenaria siceraria etc., some minor cucurbits are also cultivated. The minor cucurbits generally found in Jammu and Himachal Pradesh includes Momordica charantia var. muricata, M. dioica, Trichosanthes cucumerina var. cucumerina, T. dioica, Luffa acutangula and Coccinia grandis. These species provide nutritious vegetables and are source of medicinally important components. While information regarding the distribution and utilization of minor cucurbits in South, central and eastern India is documented, knowledge on these aspects is missing for the minor cucurbits from North-western states, particularly Jammu and Kashmir and Himachal Pradesh. Surveys made presently on these cucurbits from Jammu and Himachal Pradesh indicated that these are cultivated to a limited extent. Except wild C. grandis which is found in abundance, wild forms of remaining taxa have been reported at few locations. Present compilation describes nutritional importance and distribution of six minor cucurbits in Jammu and H.P. as well as probable reasons responsible for their underutilization. The information provided will encourage farmers to cultivate these cucurbits on large scale and improve the acceptability of these species among the local populations.